Nilai Pendidikan Dalam Novel Negeri 5 Menara Karya Ahmad Fuadi: Kajian Sosiologi Sastra Serta Implementasinya dalam Pembelajaran di Madrasah Tsanawiyah Negeri Surakarta II - Purnomo, Andika Dwi; , Drs. Adiyana Sunanda, M.Pd; , Dra. Main Sufanti, M. Hum (2016)
The aims of this research are to (1) describe the sosio-historical background Ahmad uadi, (2)the building blocks of novel Negeri 5 Menara (3) education value in Negeri 5 Menara novel by Ahmad Fuadi, (4) the implementation of Negeri 5 Menara novel in studying at Madrasah Tsanawiyah Negeri Surakarta II. The research method uses descriptive qualitative. This research data is sentences and paragraphs that have educational value, while the source data is a novel Negeri 5 Menara and curriculum syllabus 2013. Technique for collecting data use book technique and field note. Then, technique for analyzing data uses dialectic method. The result of this study indicate (1) novel Negeri 5 Menara influenced by the socio-historical background Ahmad Fuadi namely Maninjau, (2) analysis of the building blocks of a literary work, the theme of the novel Negeri 5 Menara is serious about dreams. The forms of this education are academic education and nonacademic education. The plot is straight plot (3) that in Negeri 5 Menara there are education values, such as moral value, religion value and social value. First, in moral value there are some characteristics such as discipline, never give up, and responsible. Then, in religion value, there are some good personalities like sincere, piety, and having good prejudice to Allah SWT. Last, in social value, there are some characteristics such as help and togetherness. (4) this research can be implemented in studying at Madrasah Tsanawiyah Negeri Surakarta II, especially for VIII class which refer to KD 3.1 Understanding text moral story/fable, reviews, discussions, procedures stories, biographies and stories both orally and in writing. As well as trough KD 4.1 Capturing text moral meaning of the story/fable, reviews, discussions, procedures stories, biographies and stories both orally and in writing. In addition, researchers also observed students activity, evaluation, student responses to the instructional materials and teacher responses to the teaching materials. Sociology of Literature, Negeri 5 Menara, Education Value, Studying of Literature